Revealing the Meaning of Gratitude in Qasidah Lisānī Bi Hamdillah by Habib Ali al-Habsyi (Riffaterre’s Semiotic Analysis) - Mubin, A. Faizul; Isra H, Nurul; Hakim, Lukmanul; Anwar, Nirwan (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
تهدف هذه الدراسة إلى استكشاف معاني الشكر في قصيدة "لساني بحمد الله" للحبيب علي الحبشي باستخدام نظرية سيميائية لريفاتير. تسلط القصيدة “لساني بحمد الله” الضوء على أهمية الشكر الصادق لله على نعمه الوافرة، وهو موضوع ذو أهمية ودلالة كبيرة في حياة المسلمين. لتعميق فهم معنى وأهمية هذه القصيدة، تعتمد الدراسة باستخدام نظرية سيميائية لريفاتير، الذي يؤكد على التنصل النصي وتفسير النصوص كعملية ديناميكية. يشمل هذا النهج أربعة جوانب رئيسية: انقطاع التعبير، وأساليب القراءة الهيرستية والتأويلية، ومفهوم المصفوفات والنماذج والمتغيرات، بالإضافة إلى تشكيل الهيبوغرام. تعتبر هذه دراسة وصفية كيفية. تشمل مصادر البيانات دراسات الأدب، حيث تستخدم البيانات الأساسية من نص قصيدة "لساني بحمد الله"، والبيانات الثانوية من الكتب والمقالات العلمية ذات الصلة. تشمل تقنيات جمع البيانات القراءة والمذكرات ووصف النقاط الرئيسية المتعلقة بموضوع الدراسة. يتم تحليل البيانات وفقًا لمنظور مايلز وهبيرمان، مما يشمل تقليص البيانات، عرضها، واستخلاص الاستنتاجات. تشير النتائج إلى أن قصيدة "لساني بحمد الله" لا تعد مجرد تعبير شخصي عن شكر المؤلف فحسب، بل تعد أيضًا وسيلة دعوية تذكر القراء بأهمية تقدير نعم الله، والتوكل عليه، واتباع خطى النبي محمد صلى الله عليه وسلم. من خلال التحليل الدلالي لريفاتير، يتم كشف معنى الشكر في هذه القصيدة كموضوع عميق وشامل، يعكس العلاقة الروحية الوثيقة بين الإنسان وخالقه. Abstract This research aims to explore the meaning of gratitude in the qasidah “Lisānī Bi Hamdillah” by Habib Ali al-Habsyi through Riffaterre’s semiotic approach. The qasidah “Lisānī Bi Hamdillah” emphasizes the importance of sincere gratitude to Allah for His abundant blessings a theme that is both relevant and significant in the lives of Muslims. To deepen the understanding of the meaning and significance of this qasidah, the research employs Riffaterre’s semiotic approach, which emphasizes intertextuality and the interpretation of texts as a dynamic process. This approach includes four main aspects: discontinuity of expression, heuristic and hermeneutic reading methods, the concept of matrices, models, and variants, and the formation of hypograms. This is a qualitative, descriptive study. Data sources consist of literature reviews, with primary data derived from the text of the qasidah “Lisānī Bi Hamdillah” and secondary data from relevant books and scholarly articles. Data collection techniques include reading, note-taking, and describing key points related to the research topic. Data analysis follows Miles and Huberman’s perspectives, encompassing data reduction, display, and conclusion drawing. The findings indicate that the qasidah “Lisānī Bi Hamdillah” serves not only as the poet’s personal expression of gratitude but also as a means of da’wah reminding readers of the importance of appreciating Allah’s blessings, relying on Him, and following the footsteps of Prophet Muhammad. Through Riffaterre’s semiotic analysis, the meaning of gratitude in this qasidah is revealed as a profound and comprehensive theme, reflecting the close spiritual relationship between humans and their Creator.